Influence of Service Quality Towards Customer Satisfaction Level Study At PT. Murakata Lestari Air Minum (Perseroda) Barabai District, Hulu Sungai Tengah Regency - Nurul Hasanah; Ary Yudianto; Haris Fadillah; Muhammad Egi Turahman (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2026)
This research analyzes the influence of service quality on customer satisfaction at PT. Air Minum Murakata Lestari (PERSERODA) in Barabai District, Hulu Sungai Tengah Regency. The availability of quality clean water is crucial, and service quality determines the company's reputation and customer satisfaction. The study aims to identify and analyze the impact of service quality on customer satisfaction. Employing a quantitative approach with a survey method, this research involved 20 customer respondents. Data were analyzed using simple linear regression, validity, reliability, normality tests, F-test, t-test, and determination (R2). The results indicate that service quality significantly and positively influences customer satisfaction, with a regression test significance value of 0.003 < 0.05, 64.279 > 3.55, and 7.069 > 1.724). Thus, the alternative hypothesis Ha is accepted, and the null hypothesis Ho is rejected. Service quality explains 41% of the variation in customer satisfaction. This study emphasizes the importance of service quality in shaping customer satisfaction for clean water providers, offering strategic input for service improvement tailored to customer needs